2014
DOI: 10.3171/2014.6.peds13682
|View full text |Cite
|
Sign up to set email alerts
|

Utility of surveillance imaging after minor blunt head trauma

Abstract: Object Nonoperative blunt head trauma is a common reason for admission in a pediatric hospital. Adverse events, such as growing skull fracture, are rare, and the incidence of such morbidity is not known. As a result, optimal follow-up care is not clear. Methods Patients admitted after minor blunt head trauma between May 1, 2009, and April 30, 2013, were identified at a single institution. Demographic, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
1
7
0
3
Order By: Relevance
“…As shown above, PHI was strongly associated with the type of TBI. Similar to previous studies, we found that children with mild TBI yielding normal cranial CT scans ( 19 , 20 ) or exhibiting ISFs ( 6 , 21 , 22 ) were at very low risk for PHI and at an extremely low risk of neurosurgical intervention. In our present study, 33 patients with initial normal cranial CT scans and 49 with ISFs underwent repeat CT scans, and 1 patient in each group developed PHI.…”
Section: Discussionsupporting
confidence: 90%
“…As shown above, PHI was strongly associated with the type of TBI. Similar to previous studies, we found that children with mild TBI yielding normal cranial CT scans ( 19 , 20 ) or exhibiting ISFs ( 6 , 21 , 22 ) were at very low risk for PHI and at an extremely low risk of neurosurgical intervention. In our present study, 33 patients with initial normal cranial CT scans and 49 with ISFs underwent repeat CT scans, and 1 patient in each group developed PHI.…”
Section: Discussionsupporting
confidence: 90%
“…We have used the same databases and similar methodology for prior studies of patients in our health care system. 7,8,23,26 Demographic data fields were collected at the time of admission (index admission) and included age, primary language, race/ethnicity, zip code, and primary payer status (public assistance, self-pay vs private insurance). All of the radiology reports for each patient during the index admission were reviewed manually.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Recent literature has shown that a low percentage of children with severe injury mechanisms require emergency neuroimaging 20 and has focused on reducing the number of unneeded CT scans in children. 8,24 With the negative predictive value of a normal head CT scan for neurosurgical intervention being 100%, 14 there is great incentive to reduce the number of children undergoing negative imaging because even children with mild TBI and intracranial hemorrhage are at a low risk for deterioration. 13 A recent study examining 312 pediatric patients with neurologist-diagnosed PTE (defined as 2 or more unprovoked seizures) revealed that only 17% of these patients had suffered mild TBI.…”
Section: Future Directionsmentioning
confidence: 99%
“…9 Moreover, the routine use of post-head injury surveillance imaging has been considered controversial in terms not only of cost, but also efficacy in identifying those who require operative intervention. 10 Despite these facts, the determination of neurochemical markers does not appear to be available routinely as either a diagnostic or prognostic markers of cerebral injury in primary or secondary care in the UK. Such information may be useful to set standards where elevations are observed post-head injury, providing a referral system to manage safe and effective return-to-play and prevention of any associated long-term sequelae.…”
Section: Introductionmentioning
confidence: 99%